Matrix approach to detectability of discrete event systems. Issue 12 (August 2019) - Wang, Biao; Feng, Jun-e; Meng, Min
Abstract: This paper studies the detectability problem of discrete event systems (DESs), and devotes to providing a synthetical method to cope with multiple cases, including (partial) event observation and/or partial state observation. By using the semi-tensor product method, two equivalent types of algebraic expressions are presented for DESs, based on which reachability of DESs is investigated in detail and a new tool called detection matrix is defined. Then, four matrix-based necessary and sufficient conditions are derived for checking different kinds of detectability. Finally, for better presentation, two examples are shown to demonstrate that the theoretical results are efficient.